No barrier to care, yet disparities in the HIV care continuum in France: a nationwide population study. (10th March 2021) - Cuzin, Lise; Allavena, Clotilde; Cotte, Laurent; Delpierre, Cyrille; Huleux, Thomas; Palich, Romain; Delobel, Pierre; Raffi, François; Cabié, André
Abstract: Objectives: Even in an 'optimal' health system, patients' characteristics may have an impact on their care. We investigated whether age, gender and place of birth have an impact in the HIV care continuum in France, a country with a universal free healthcare system. Methods: We estimated differences in the 5 year restricted mean percentage of person-time spent (i) in care, (ii) receiving ART and (iii) on ART and virally suppressed among 2432 (30.2%) women, 3925 MSM (48.7%) and 1709 men who have sex with women (MSW; 21.2%) entering care in the Dat'AIDS French prospective cohort between 1 January 2013 and 31 December 2017. Trial registration: Clinicaltrials.gov reference NCT02898987. Results: Men and women spent 85.6% and 82.8% of person-time on ART and 69.9% and 65% suppressed, respectively. MSM, MSW and women spent 86.9%, 82.6% and 82.8% of person-time on ART and 72.5%, 63.7% and 65% suppressed, respectively. Patients born in France (47%) and patients born abroad spent 87.9% and 81.9% of person-time on ART and 74.6% and 62.9% suppressed, respectively. Young men born abroad were found to spend the smallest person-time with non-detectable viral load (53% for MSW and 58.1% for MSM). Conclusions: Despite free access to care and universal ART in France, disparities remain in the HIV continuum care across age, country of birth and way of HIV acquisition. Clinical and public health interventions targeting specific patients' conditions are needed.